KOMPETENSI PROFESSIONAL GURU QUR’AN HADITS DI MTsN 8 PIDIE - Juairiah Umar (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2019)
Professional competence is the ability associated with the completion of teacher assignments. The professional competence of the Hadith Qur'an teachers is to develop plans for both objectives, a content of learning materials, methods, and techniques, as well as assessment, are the main elements that must be minimally present in every implementation of learning. How high is the relationship between the professional competence of the Qur'an Hadith teachers and the planning and implementation of learning in Pidie MTsN? This qualitative research collects data through observation, interviews, questionnaires, documentation and analyzed through descriptive analytics. The questionnaire was analyzed using Rating Scala, the number of respondents was 10, the items were also 10. The results showed the professional competence of the Qur'an 85% hadith approached "always", for Planning 10 respondents, item 10, the result was 74% approach quite well, while Implementation respondent 10, item 13, the result is 82% approaching very well, meaning the professional competence of the Qur'an teacher Hadith is closely related to the RPP and the implementation of learning.